Associations of maternal alcohol and non-prescribed substance use with early child growth - Yukiko Washio; Zugui Zhang; Mona Lisa Baishya; Marilyn T. Lake; Bronwyn Myers; Nadia Hoffman; Elizabeth Goddard; Heather J. Zar; Dan J. Stein; Petal Petersen Williams (South African Journal of Psychiatry)
Background: Perinatal alcohol and non-prescribed substance use may be detrimental to foetal and infant growth.